2017
DOI: 10.1016/j.smim.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing: How modulating LTB 4 actions restore host defense in homeostasis or disease

Abstract: The ability to regulate inflammatory pathways and host defense mechanisms is critical for maintaining homeostasis and responding to infections and tissue injury. While unbalanced inflammation is detrimental to the host; inadequate inflammation might not provide effective signals required to eliminate pathogens. On the other hand, aberrant inflammation could result in organ damage and impair host defense. The lipid mediator leukotriene B4 (LTB4) is a potent neutrophil chemoattractant and recently, its role as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 104 publications
(124 reference statements)
2
42
0
1
Order By: Relevance
“…We and others have shown that LTB4 is required for phagocytosis and antimicrobial effector functions by increasing reactive oxygen and nitrogen species secretion and defensin production during infection by gram-positive and negative bacteria, protozoan parasites, and viruses (16)(17)(18)(19)39). Although LTB4 is an essential homeostatic mediator of the inflammatory response, high and sustained LTB4 production has been associated with inflammatory diseases and metabolic dysfunctions (36,40), supporting the idea that abundant and chronic circulating LTB4 levels are harmful to the host. Moreover, exaggerated LTB4 is responsible for an aberrant TNF- production that drives susceptibility to mycobacterial infection in a zebrafish model.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that LTB4 is required for phagocytosis and antimicrobial effector functions by increasing reactive oxygen and nitrogen species secretion and defensin production during infection by gram-positive and negative bacteria, protozoan parasites, and viruses (16)(17)(18)(19)39). Although LTB4 is an essential homeostatic mediator of the inflammatory response, high and sustained LTB4 production has been associated with inflammatory diseases and metabolic dysfunctions (36,40), supporting the idea that abundant and chronic circulating LTB4 levels are harmful to the host. Moreover, exaggerated LTB4 is responsible for an aberrant TNF- production that drives susceptibility to mycobacterial infection in a zebrafish model.…”
Section: Discussionmentioning
confidence: 99%
“…LTB 4 induces the release of potent antimicrobial products such as α‐defensins and cathelicidins, lysosomal enzymes, activation of NADPH oxidase, and NO production to enhance bacterial killing . 5‐LO and LTB 4 are important in killing several pathogens, including Klebsiella pneumoniae , Mycobacterium tuberculosis , and Leishmania amazonensis . In addition, exogenous administration of LTB 4 was demonstrated to enhance innate immune responses against several pathogenic bacteria .…”
Section: Discussionmentioning
confidence: 99%
“…LTB 4 induces the release of potent antimicrobial products such as α-defensins and cathelicidins, lysosomal enzymes, activation of NADPH oxidase, and NO production to enhance bacterial killing. 46 51 In addition, exogenous administration of LTB 4 was demonstrated to enhance innate immune responses against several pathogenic bacteria. 44,51 We have previously shown that 5-LO and BLT1 are critical for in vitro macrophage phagocytosis of B. burgdorferi 22,39 ; however, neutrophil phagocytosis was minimally impacted, similar to the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of utmost importance for the immune response is the 5-LOXmediated generation of leukotriene A4 (LTA4) and its further transformation, by LTA4 hydrolase, into the pro-inflammatory leukotriene B4 (LTB4). LTB4 regulates inflammatory pathways and immune responses against infection and tissue injury (Brandt and Serezani, 2017).…”
Section: Ndga Is a Pan-lipoxygenase Inhibitormentioning
confidence: 99%